(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article examines the potential of the Chinese diaspora abroad. Investigate the influence of the People’s Republic of foreign economic strategy of «Going to the outside» on the investment activity of Chinese enterprises abroad, the export of labor. Keywords: China, migrants, reform, economic strategy, migration policy.